"Un viaje por los saberes del pueblo indígena Pijao” material didáctico para el reconocimiento, valoración y respeto de la diversidad étnica y cultural de Colombia. (2022)
This paper aims to provide a proposal for a didactic material which seeks to promote and visualize the Pijao indigenous' cultural wealth, to contribute the recognition, appreciation and respect of Colombian's ethnic and cultural diversity from school contexts. For the design of the didactic material “Un viaje por los saberes del pueblo indígena Pijao: los hijos de Ta y Taiba”, various needs were considered regarding the visibility of indigenous people, theorical model focus on ethnic and cultural diversity, the curricular guidelines and basic standards of the language areas, social science and citizen competencies, and the indigenous' worldview. As a result, an interactive teaching material was obtained, it is divided into three units that highlight and make visible some of the most important historical and cultural knowledge of the Pijao's people. This was submitted to the evaluation of expert pairs and pilotages. The results are analyzed, and it is concluded that the material meets the objective stated in its content.